THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND ACADEMIC ACHIEVEMENT AMONG UNDERGRADUATE STUDENTS IN KAZAKHSTAN - Lyudmila Nikolayevna Fillipova,; Darkhan Nurlanovich Bilyalov, (Scientific Journal of Pedagogy and Economics, 2020)
While academic achievement and performance of students in higher education settings continue to be crucial, there is a growing emphasis internationally on the acquisition of non-cognitive skills of future specialists. Perhaps, one of the most widely discussed soft skills is Emotional Intelligence (“EI”). Despite being recognized as an independent concept since the second part of the twentieth century, most experts in the spheres of psychology, education and management still find this area somewhat ambiguous. Several studies focused on the relationship between emotional intelligence and academic achievement before. However, very little research in this sphere has been conducted in Kazakhstan. While the gap in scholarship is evident, the praxis is also underdeveloped. This study utilized a cross-sectional correlational design [1,2,3]. The purpose of the study was to identify the relationship between emotional intelligence and academic achievement among undergraduate students. To achieve this, we administered the ESAP (Emotional Skills Assessment Process) questionnaire that focuses on four main competencies: interpersonal, leadership, self-management, and intrapersonal. We used the self-reported indicators to obtain information about students’ academic achievement. We collected data in two Kazakhstani universities for confidentiality purposes called the Autonomous University and the Regional University. The sample consisted of 239 undergraduate students, 141 and 98 undergraduates from two universities (Regional and Autonomous), respectively. The sample was recruited on a non-probability basis due to the voluntary participation in the research study and the unavailability of the sampling frames. We used the Statistical Package for the Social Sciences (SPSS) for descriptive, inferential, and correlational statistical analyses of the collected data. The study presents information on the general emotional intelligence levels of undergraduate students of two universities. Similarly, the research study identifies three levels of academic achievement of students: high, average, and low achieving and establishes their correlation with emotional intelligence competencies and levels. Furthermore, the study explores students’ emotional intelligence levels differentiated by such independent variables as their age and gender.